Primary and secondary myelofibrosis: ophthalmological manifestations at onset and during therapy - O. Yu. Vinogradova; L. B. Egoryan; D. I. Shikhbabaeva; A. L. Neverova; M. M. Pankrashkina; L. K. Moshetova (Онкогематология, 2025)
Background. There is little information about ophthalmological manifestations of myelofibrosis (MF), their dependence on hematological, morphological, genetic parameters, and eye damage during therapy, and there are no publications on eye changes during targeted therapy.   Aim. To study the spectrum and frequency of ophthalmological manifestations of primary, post‑polycythemic, post‑thrombocythemic MF at the diagnosis and during therapy.   Materials and methods. A prospective single‑center controlled study included 128 people: 98 patients with primary, post‑polycythemic, post‑thrombocythemic MF in the chronic phase (17 at onset, 30 long‑term receiving hydroxycarbamide, 51 long‑term receiving ruxolitinib), observed at the botkin Hospital and 30 healthy participants of the control group. Ophthalmological and genetic studies were conducted.   Results. It has been established that ophthalmologic manifestations accompany MF already at the onset of the disease: significantly higher frequency of retinal angiopathy and angioretinopathy, decreased retinal sensitivity in the macular area, remodeling of the foveolar avascular zone (increased perimeter, decreased circumference index), low vascular and perfusion density of the retina, choroid and optic disc, decreased thickness of the subfoveolar choroid compared with the control group. Ruxolitinib MF therapy is safe for the visual organ according to the assessed parameters and has a positive therapeutic effect compared with MF onset and hydroxycarbamide therapy: such patients demonstrated smaller perimeter of the foveolar avascular zone, higher vascular and perfusion density of the retina, choroid and optic disc. There was a statistically significant association between an increased frequency of retinal angiopathy and angioritinopathy with a platelet count less than 100 × 109 / L, erythrocytes less than 3.7 × 1012 / L, hemoglobin level less than 100 g / L, high degree of fibrosis (MF‑3), presence of the JAK2 v617F mutation; the increased frequency of angiopathy associated with the leukocyte count less than 4.0 × 109 / L and more than 9.0 × 109 / L, erythrocytes more than 5.1 × 1012 / L, high risk according to DIPSS (Dynamic International Prognostic Scoring System). Vascular and perfusion density of the choriocapillary layer in patients at the onset of primary MF significantly correlated with the level of platelets and hemoglobin.   Conclusion. The conducted search for ophthalmological manifestations on a large cohort of MF patients at the onset and during therapy is largely innovative and requires further research, and also confirms the need to include a consultation with an ophthalmologist in the examination algorithm for MF patients.